2016
DOI: 10.1002/biot.201500301
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐to‐cell heterogeneity emerges as consequence of metabolic cooperation in a synthetic yeast community

Abstract: Cells that grow together respond heterogeneously to stress even when they are genetically similar. Metabolism, a key determinant of cellular stress tolerance, may be one source of this phenotypic heterogeneity, however, this relationship is largely unclear. We used self‐establishing metabolically cooperating (SeMeCo) yeast communities, in which metabolic cooperation can be followed on the basis of genotype, as a model to dissect the role of metabolic cooperation in single‐cell heterogeneity. Cells within SeMeC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…Further, we tested for copy number effects, and found that the expression of HIS3, LEU2, MET15 and URA3 from the minichromosome fully suffices the biosynthetic needs 33 . A situation in which all cells are provided with a high concentration of nutrients, as would occur with media supplementation, may also be less native to cells community where, usually, a certain fraction of cells are dependent on metabolite exchange 25, 45 . For the typical experiment, the constraints arising from segregation of a single-copy minichromosome that restores auxotrophy, are hence much smaller compared to the problems caused by the use of nutrient supplemented media and auxotrophic strain backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, we tested for copy number effects, and found that the expression of HIS3, LEU2, MET15 and URA3 from the minichromosome fully suffices the biosynthetic needs 33 . A situation in which all cells are provided with a high concentration of nutrients, as would occur with media supplementation, may also be less native to cells community where, usually, a certain fraction of cells are dependent on metabolite exchange 25, 45 . For the typical experiment, the constraints arising from segregation of a single-copy minichromosome that restores auxotrophy, are hence much smaller compared to the problems caused by the use of nutrient supplemented media and auxotrophic strain backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for a long time that a subpopulation of plasmid free cells can co-grow alongside plasmid containing cells, despite using nutrient selection 2, 4648 . In our lab we have exploited this property to study metabolite exchange interactions between cells, and developed a system of self-establishing metabolically cooperating communities (SeMeCo) in which a series of auxotrophs cooperate to enable the growth of a yeast community 25, 45 . This system exploits plasmid segregation, starting from an initially self-supporting cell, that grows progressively into an increasingly heterogeneous population, which is able to proliferate on the basis of nutrient exchange occuring between yeast cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, different cells of the community exhibit 42 metabolic interdependencies, presumably to balance out trade-offs arising from resource sharing. While 43 this concept has been demonstrated for example, in synthetically engineered systems, where required 44 metabolic dependencies are created between non-isogenic cells (Campbell et al, 2016(Campbell et al, , 2015, this has 45 been exceptionally challenging to demonstrate within a clonal community of cells. We recently 46 enables a self-organizing system based on non-limiting and limiting resources, which creates organized 70 phenotypic heterogeneity in cells.…”
Section: Introduction: 23mentioning
confidence: 99%
“…This reduction of global productivity can often be ascribed to the formation of a specific subpopulation of cells with vanished or discounted production capacity (Delvigne, Zune, Lara, Al‐Soud, & Sorensen, ). It has been recently reported that this cell‐to‐cell heterogeneity arises from metabolic cooperation (Campbell, Vowinckel, & Ralser, ), and metabolite dynamics in response to the extracellular environment plays a vital role in regulating biomass growth and product formation in industrial practices (A. C. Schmitz, Hartline, & Zhang, ). It is hence indispensable to understand how metabolic fluxes are intricately coordinated by complex regulatory mechanisms such as gene‐metabolite association maps (Zampieri & Sauer, ), posttranslational modifications, for example, enzyme phosphorylation or acetylation (Gerosa & Sauer, ).…”
Section: Introductionmentioning
confidence: 99%